From Wide Cognition to Mechanisms: A Silent Revolution - Miłkowski, Marcin; Clowes, Robert; Rucińska, Zuzanna; Przegalińska, Aleksandra; Zawidzki, Tadeusz; Krueger, Joel; Gies, Adam; McGann, Marek; Afeltowicz, Łukasz; Wachowski, Witold; Stjernberg, Fredrik; Loughlin, Victor; et al. (Frontiers in Psychology, 2018)
In this paper, we argue that several recent ‘wide’ perspectives on cognition (embodied, embedded, extended, enactive, and distributed) are only partially relevant to the study of cognition. While these wide accounts override traditional methodological individualism, the study of cognition has already progressed beyond these proposed perspectives towards building integrated explanations of the mechanisms involved, including not only internal submechanisms but also interactions with others, groups, cognitive artifacts, and their environment. The claim is substantiated with reference to recent developments in the study of “mindreading” and debates on emotions. We claim that the current practice in cognitive (neuro)science has undergone, in effect, a silent mechanistic revolution, and has turned from initial binary oppositions and abstract proposals towards the integration of wide perspectives with the rest of the cognitive (neuro)sciences.